Anthracyclines and regional myocardial damage in breast cancer patients. A multicentre study from the Working Group on Drug Cardiotoxicity and Cardioprotection, Italian Society of Cardiology (SIC). (12th January 2021) - Zito, Concetta; Manganaro, Roberta; Cusmà Piccione, Maurizio; Madonna, Rosalinda; Monte, Ines; Novo, Giuseppina; Mercurio, Valentina; Longobardo, Luca; Cadeddu Dessalvi, Christian; Deidda, Martino; Pagliaro, Pasquale; Spallarossa, Paolo; et al.
Abstract: Aims: In breast cancer (BC) patients treated with anthracyclines-based therapies, we aim at assessing whether adjuvant drugs impact cardiac function differently and whether their cardiotoxicity has a regional pattern. Methods and results: In a multicentre study, 146 BC patients (56 ± 11 years) were prospectively enrolled and divided into three groups according to the received treatments: AC/EC-Group (doxorubicin or epirubicin + cyclophosphamide), AC/EC/Tax-Group (AC/EC + taxanes), FEC/Tax-Group (fluorouracil + EC + taxanes). Fifty-six patients of the total cohort also received trastuzumab. Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) were calculated before starting chemotherapy (T0 ), at 3 months (T3 ), at 6 (T6 ), and 12 months (T12 ). A ≥10% drop of EF, while remaining within the normal range, was reached at T6 in 25.3% of patients from the whole cohort with an early decrease only in FEC/Tax-G roup ( P = 0.04). A ≥15% GLS reduction was observed in many more (61.6%) patients. GLS decreased early both in the whole population ( P < 0.001) and in the subgroups. The FEC-Tax Group showed the worst GLS at T6 . Trastuzumab further worsened GLS at T12 ( P = 0.031). A significant reduction of GLS was observed in all LV segments and was more relevant in the anterior septum and apex. Conclusions: The decrease of GLS is more precocious and pronounced in BC patients who received FEC + taxanes. Cardiac function further worsens after 6 months of adjuvant trastuzumab. All LV segments are damaged, with the anterior septum and the apex showing the greatest impairments.